Effects of Intermittent Drought on the Essential Oil Yield, Contents, and Nutrient Status of Mentha longifolia (L.) Huds. Issue 3 (4th May 2022) - Singh, Ruby; Luxmi, Savita; Charak, Aditi; Gochar, Rajendra; Kumar, Amit; Gandhi, Sumit G.; Bhanwaria, Rajendra
Abstract: Mentha longifolia is one of the important aromatic crop cultivated for its essential oil. The experiment was conducted to determine the effects of intermittent drought on the essential oil yield, composition, and nutrient status in M. longifolia . Initially, experimental plants were divided into two group: 'irrigated' and 'drought'. The 'irrigated group was watered normally, while the 'drought' group was not watered for seven days. Subsequently, both the groups were irrigated during the recovery period. Further, both groups were divided into two subgroups with non-irrigated and irrigated plants for seven days. In each cycle, samples were taken on 0, 7, 14, 21 days (first, second, and third cycle). Results indicated that the essential oil yield (ml/100- gram plant material) was increased under drought stress from 0.6 to a maximum of 0.9, while it showed a reduction in limonene, d-carvone percentage and percentage of nutrients (nitrogen and potassium) in the plants with non-significant change in phosphorous concentration. Also, the highest values of neodihydrocarveol (26.4%) and c-dihydrocarvone (11.43%) were determined by Gas Chromatography/Mass Spectrometry (GC/ MS) under third cycle. Our findings provide critical insights and directions for appropriate irrigation schedule so as to maximize the essential oil yield.